2003
DOI: 10.1046/j.1365-2427.2003.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Allocation strategies in crustacean stoichiometry: the potential role of phosphorus in the limitation of reproduction

Abstract: Summary 1. Elemental composition (carbon : nitrogen : phosphorus, C : N : P) was analysed in eggs and juveniles of two crustaceans, Daphnia magna (Cladocera) and the crayfish Astacus astacus (Decapoda). Stoichiometry was also analysed for the carapace, muscle tissue, hepatopanchreas and gills of Astacus. 2. For both species the C : P ratio was significantly higher in eggs than juveniles, but there was a constant, homeostatic elemental ratio in eggs during embryogenesis (Astacus) and with different C : N : P in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 40 publications
6
63
2
Order By: Relevance
“…In contrast, the C : P ratio of Daphnia females was only slightly smaller than that of their eggs; being their N : P much smaller and the C : N much higher because of a higher N content in the eggs. A higher C : P ratio in Daphnia eggs than juveniles was found by Faerøvig and Hessen (2003); however, the C : P ratios were substantially lower for both Daphnia magna and Astracus (120 for both species) than in our study. The C : P ratios measured in this study are closer to those found by Sterner and Schulz (1998), who reported egg C : P ratios for Daphnia magna and Daphnia obtusa of 192 and 310, respectively, D. magna eggs having almost twice the C : P ratio of adult females (83).…”
Section: Discussioncontrasting
confidence: 77%
“…In contrast, the C : P ratio of Daphnia females was only slightly smaller than that of their eggs; being their N : P much smaller and the C : N much higher because of a higher N content in the eggs. A higher C : P ratio in Daphnia eggs than juveniles was found by Faerøvig and Hessen (2003); however, the C : P ratios were substantially lower for both Daphnia magna and Astracus (120 for both species) than in our study. The C : P ratios measured in this study are closer to those found by Sterner and Schulz (1998), who reported egg C : P ratios for Daphnia magna and Daphnia obtusa of 192 and 310, respectively, D. magna eggs having almost twice the C : P ratio of adult females (83).…”
Section: Discussioncontrasting
confidence: 77%
“…Nutrient ratios also are important because growth requires different relative amounts of C, N, and P, and other elements (Elser et al 1996, Sterner and. Furthermore, somatic growth may have different elemental requirements than gamete production, especially with reference to P (Vrede et al 1999, Faerøvig andHessen 2003). Because %C and %N did not vary markedly across ontogeny, the C:N ratio also did not vary much for the 8 taxa examined in our study.…”
Section: Patterns Of C N and P Contentmentioning
confidence: 60%
“…For P measurement, individual insects were weighed as above, placed in 22-mL glass scintillation vials, pulverized with a metal spatula, capped with a lid containing a Teflon septum, and chemically digested in an autoclave for 1 h at 120uC by the method of Faerøvig and Hessen (2003). The minimum mass required for P measurement was 10 mg (assuming 1% P content).…”
Section: Chemical Analysesmentioning
confidence: 99%
“…Low ratios of environmental N/P and C/P favor species with very high rates of growth (5) and may induce shifts in species communities (6,7). The GRH has strong experimental support in freshwater ecosystems (2), with a few exceptions related to the allocation of nutrients to functions other than growth (8)(9)(10). In terrestrial ecosystems, however, the direct application of the GRH frequently fails or is accomplished incompletely (2,11).…”
mentioning
confidence: 99%